Antihemolytic Efficiency of Chlorpromazine under Posthypertonic Shock and Glycerol Removal from Erythrocytes after Thawing - Semionova, Yekaterina A.; Zemlyanskikh, Nina G.; Orlova, Nataliya V.; Shpakova, Nataliya M. (Problems of Cryobiology and Cryomedicine, 2017)
The chlorpromazine effect on sensitivity of human erythrocytes to the action of posthypertonic shock and their resistance at glycerol removal from the cells exposed to freeze-thawing has been studied in our research. It has been shown that under conditions of posthypertonic shock of erythrocytes (at 0°C) the chlorpromazine reduced a hemolysis level in 3.7 times, and in case of 600 µmol/l concentration its maximum antihemolytic activity was 73 ± 6%. The application of chlorpromazine during removal of glycerol from frozen-thawed erythrocytes enabled to reduce the cell damage by 2.5–3 times. The values of antihemolytic activity of chlorpromazine in both cases were quite similar. Results of the investigation of chlorpromazine efficiency in the model experiment and under the real conditions of erythrocyte freeze-thawing (under glycerol removal from the cells) allow to conclude about the applicability of this model (posthypertonic shock) in the further studies. Probl Cryobiol Cryomed 2017; 27(1): 51–60